2017
DOI: 10.1159/000478930
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Perineum during Delivery with the Kiwi Omnicup: Effects of Mediolateral Episiotomy on Anal Sphincter Tears in Nulliparous Women

Abstract: Aim: The main objective of this study was to evaluate the association of mediolateral episiotomy with severe perineal trauma during Kiwi omnicup vacuum delivery. Methods: This retrospective study analyzed all Kiwi omnicup vacuum deliveries between 2010 and 2015 in nulliparous women. Secondary outcomes of interest included frequency of genital tract trauma, outcome of Kiwi extraction and influence on neonatal parameters. Results: A total of 572 nulliparous women who were delivered with the aid of vacuum were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…The number needed to treat to prevent one obstetric anal sphincter injury during vacuum‐assisted delivery was found to be 50. This finding is supported by previous studies, which reported a decrease in obstetric anal sphincter injuries when episiotomy was used in operative vaginal deliveries 8, 25, 28, 29. Jangö et al report a number needed to treat of 23 mediolateral episiotomies and Raisänen et al report a number needed to treat of 66 lateral episiotomies to prevent one case of obstetric anal sphincter injury in vacuum‐assisted deliveries, thus favoring more frequent use of episiotomy in such cases 28, 30.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The number needed to treat to prevent one obstetric anal sphincter injury during vacuum‐assisted delivery was found to be 50. This finding is supported by previous studies, which reported a decrease in obstetric anal sphincter injuries when episiotomy was used in operative vaginal deliveries 8, 25, 28, 29. Jangö et al report a number needed to treat of 23 mediolateral episiotomies and Raisänen et al report a number needed to treat of 66 lateral episiotomies to prevent one case of obstetric anal sphincter injury in vacuum‐assisted deliveries, thus favoring more frequent use of episiotomy in such cases 28, 30.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is supported by previous studies, which reported a decrease in obstetric anal sphincter injuries when episiotomy was used in operative vaginal deliveries. 8,25,28,29 Jangö et al report a number needed to treat of 23 mediolateral episiotomies and Raisänen et al report a number needed to treat of 66 lateral episiotomies to prevent one case of obstetric anal sphincter injury in vacuum-assisted deliveries, thus favoring more frequent use of episiotomy in such cases. 28,30 In forceps-assisted vaginal delivery, we could not find a protective effect of mediolateral episiotomy.…”
Section: Adjusted a Or (95% Ci)mentioning
confidence: 99%
“…Perineal injuries mean injury to perineal muscles or anal sphincter and may be to the labia, vagina, urethra, and clitoris. This may occur spontaneously during a vaginal birth, or from the trauma of an operative delivery or by an episiotomy (Bodner-Adler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Though several risk factors have been associated with OASI, including operative vaginal delivery, nulliparity, macrosomia, Asian race, shoulder dystocia, and episiotomy, these factors are often considered unmodifiable, particularly in light of the alternative—a cesarean birth. 9 10 11 12 13 The length of the second stage of labor has been associated with anal sphincter injury in some but not all studies, likely at least in part because of the difficulty in separating the impact of fetal malposition, operative vaginal delivery, and prolonged second stage that frequently cooccur. Given the recent emphasis on more permissive time limits for the second stage as a part of efforts to decrease primary cesarean deliveries, 14 understanding the relationship between second-stage length and anal sphincter injury is an important part of counseling women regarding risks and benefits of options for management in the second stage.…”
mentioning
confidence: 99%